DEVELOPMENT AND VALIDATION OF AN EDUCATIONAL HEARING CONSERVATION PROGRAMME FOR MALAYSIAN YOUTH: Bisinglah BEB! - ISHAK, KAMARUL AKMAL; ISMAIL, NORAIDAH; RAHMAT, SARAH (Malaysian Journal of Public Health Medicine, 2021)
Exposure to leisure noise among the youth has grown into a public health concern. It was reported that attitudes and behaviours are essential factors in determining how well someone takes care of their hearing. An educational hearing conservation programme (EdHCP) can be an effective way to educate and to induce behavioural changes. The objective of this study is to develop and to validate a Malay version of EdHCP known as Bisinglah BEB! (in English: HEY! It’s Loud!) targeting the Malaysian youth. The present study comprised of four phases, namely; i) content and module development, ii) content validation, iii) content modification, and iv) pre-testing. Five learning modules were developed; Module One (Sound energy), Module Two (Anatomy and hearing mechanisms), Module Three (Hearing loss), Module Four (How loud the sound), and Module Five (How to protect our hearing). The module and contents of the programme possessed good content validity result (S-CVI/Ave value at 0.935). Several modifications were done accordingly, and agreement among the participants in pre-testing was excellent (95-100%). Bisinglah BEB! was informative and produced a high content-validity result. However, the effectiveness of the programme in changing attitude, knowledge, and behaviour towards noise exposure needs to be investigated before the real implementation in Malaysian youth.